A Case Report of Profuse Bleeding in the Lower Gastrointestinal Tract due to Dieulafoy Lesion in the Rectum - Saskia Aziza Nursyirwan; Roy Soetikno; Noto Dwimartutie; Kaka Renaldi (Acta Medica Indonesiana, 2023)
Dieulafoy lesion is a rare condition that usually occurs in cases of gastric bleeding in the upper gastrointestinal tract. However, this condition can also occur in the lower gastrointestinal tract but less frequently. The lesion is an arteriolar malformation that extends to the submucosa, causing erosion and bleeding. Meanwhile, this is a case of a 67-year-old woman presenting with a bright red bloody stool prior to admission, as well as a history of constipation which was relieved by digital stool evacuation two weeks earlier. The medical history of the patient reveals episodes of  repeated ischaemic stroke for over seven years and three months, which has led to other conditions such as right-sided paralysis, transcortical motor aphasia, and neurogenic dysphagia. The patient was routinely on antithrombotic medications, which was stopped during hospitalisation where repeated packed cell transfusion was done in order to avoid hematochezia. The patient needed the support of her caregiver most of the time since she was bedridden. Furthermore, the haemostasis and platelet function of the patient were normal. On colonoscopy, there was the discovery of a small lesion of about 3mm in her rectum, protruding into the lumen and pulsated, which was discovered to be Dieulafoy’s lesion. Subsequently, this lesion was closed using rubber band ligation, and after a month, there was no recurrence of the lower gastrointestinal bleeding.